2017
DOI: 10.1299/jbse.16-00580
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the effect of a surrounding fluid on bovine sperm motility in three dimensions

Abstract: We constructed an experimental system that can observe bovine sperm motility in three dimensions, simultaneously from the vertical and horizontal directions. The comparison of the experiments conducted using cover glass and square tubing indicates that the effect of the cover glass on the sperm motility is not negligible. Based on this result, we investigated a three-dimensional trajectory of a motile sperm in the square tubing by simultaneously observing through two high-speed cameras. In addition, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Their results indicated that the mucus was a non-Newtonian fluid. Some studies have focused on the effects of the surrounding environment (i.e., the fluid characteristics of the oviduct) on sperm motility, including the effects of fluid viscosity (Hyakutake et al, 2015a(Hyakutake et al, , 2017Katz et al, 1978;Kirkman-Brown et al, 2011;Smith et al, 2009), viscoelastic properties (Tung et al, 2015), and non-Newtonian properties (Hyakutake et al, 2015b). However, the actual viscosity of the mammalian oviductal mucus is much greater than that of fluids in these in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicated that the mucus was a non-Newtonian fluid. Some studies have focused on the effects of the surrounding environment (i.e., the fluid characteristics of the oviduct) on sperm motility, including the effects of fluid viscosity (Hyakutake et al, 2015a(Hyakutake et al, , 2017Katz et al, 1978;Kirkman-Brown et al, 2011;Smith et al, 2009), viscoelastic properties (Tung et al, 2015), and non-Newtonian properties (Hyakutake et al, 2015b). However, the actual viscosity of the mammalian oviductal mucus is much greater than that of fluids in these in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%